[tex]\bf \textit{Cofunction Identities}
\\ \quad \\
sin\left(\frac{\pi}{2}-{{ \theta}}\right)=cos({{ \theta}})\qquad
\boxed{cos\left(\frac{\pi}{2}-{{ \theta}}\right)=sin({{ \theta}})}
\\ \quad \\ \quad \\
tan\left(\frac{\pi}{2}-{{ \theta}}\right)=cot({{ \theta}})\qquad
cot\left(\frac{\pi}{2}-{{ \theta}}\right)=tan({{ \theta}})
\\ \quad \\ \quad \\
sec\left(\frac{\pi}{2}-{{ \theta}}\right)=csc({{ \theta}})\qquad
csc\left(\frac{\pi}{2}-{{ \theta}}\right)=sec({{ \theta}})[/tex]
[tex]\bf \\\\
-------------------------------\\\\
sin^2(\theta)+cos^2(\theta)=1\implies cos^2(\theta)=1-sin^2(\theta )
\\\\\\
\boxed{cos(\theta )=\sqrt{1-sin^2(\theta )}}[/tex]
[tex]\bf \\\\
-------------------------------\\\\
\cfrac{cos^2\left(\frac{\pi }{2}-x \right)}{\sqrt{1-sin^2(x)}}\implies \cfrac{\left[ cos\left(\frac{\pi }{2}-x \right)\right]^2}{cos(x)}\implies \cfrac{[sin(x)]^2}{cos(x)}\implies \cfrac{sin(x)sin(x)}{cos(x)}
\\\\\\
sin(x)\cdot \cfrac{sin(x)}{cos(x)}\implies sin(x)tan(x)[/tex]